DEVELOPMENT OF PRESENTATIOPROGRAMN LEARNING MEDIA BASED ON THE PREZI APPLICATION - Tresna Maesaroh (JOSAR (Journal of Students Academic Research), 2021)
This research was conducted based on the background of students' lack of interest andinterest in PPKn subjects, according to students PPKn subjects related to very much material,besides that in the delivery of material still using the lecture method. This causes student learningoutcomes in PPKn subjects to be not maximal.This study aims to develop learning media, presentation and feasibility of presentationmedia based on prezi application programs to be used as learning aids so students students moreeasily understand and accept the material presented.Research conducted using the Research and Development (R and D) research model withthe development method. Determination of the feasibility level of presentation media based on preapplication application program is based on validation tests of experts consisting of media andmaterial experts and small-scale trials which are then applied to the experimental class. Datacollection techniques using interviews, direct observation, documentation data, questionnaires, andtests.From the results of product validation with media experts the development of presentationlearning media based on the prezi application program, conclusions were obtained with goodcriteria, with an average value of 3.56. The results of product validation with material expertsconcluded conclusions with good criteria with an average value of 3.64, the results ofquestionnaires by students also obtained results with very good assessment criteria while the resultsof small group trials and large groups there was an increase in learning outcomes. With the resultsof the average pre-test value of the small group 37 and the average value of the post-test 85, and forthe large group the average value of the pre-test was 43.4 and the post-test average value was 85.7.